Franchise and retail management system - Rajeev Kumar, M; K. Senthil Kumar, N; Balaji, D (International Journal of Engineering and Technology, 2018)
The main concept of franchise and retail management system is to make a very user friendly environment for all the retailers and franchisee. The software will provide real-time communication between franchisees or the controlling office over the Internet. This online system will be used both at the controlling office and the franchisee centers. It will cover registration, login and order facility for franchisees etc. and store those details at the head office's centralized database. Its main application is to maintain franchisee details such as business partner details, agreement validity, meetings to be organized etc. and to integrate a number of franchisees irrespective of geographical boundaries to facilitate easy monitoring and reporting to the main office.Â